The influence of technology in the english teaching-learning process instudents of the 5th course at María Auxiliadora high school - Farfán, Andrea; Jaramillo, Martha
A short introduction about Technology, its concepts, terminology, origins, the Internet and its impact in the educational field are presented. Firstly, we refer to the influence of technology in the educational field, and specifically its impact in the classroom and the way how the teaching-learning process effectiveness has been influenced. Then, we present a research and results about the influence of technology in the English learning process at Maria Auxiliadora High School, which show the positive aspects of implementing technology, and the students and teachers´ attitude toward the use of technology. We try to prove not just the results of the study and surveys applied to the teachers and students expressed in percentages, but also their attitude towards the implementation and use of technology in the English teaching - learning process. The results show the benefits they both have had after a certain period of time, and the satisfaction they feel after this time with the results obtained. Finally, we invite the reader to think about the importance of the implementation of technology into the classes to help learners improve their English, and to the teachers to immerse themselves into an innovative way to teach, at the time their students experiment a motivating way to learn it